Peran BPOM dan BPKN dalam Memberikan Perlindungan Hukum Bagi Konsumen terhadap Peredaran Vaksin Palsu - Taufikkurrahman Taufikkurrahman (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
Based on investigation result of the Police Criminal Investigation that is found in some vaccines allegedly Spurious. Said to be Spurious because the quality provided is not equal to the quality specified by the government. The Spurious vaccines is a mixture of original vaccine coupled with the infusion so that the quality of vaccines given to children of immunization participants are not suitable dose should. The discovery of false vaccines make the anxious parents bacause the fearing of the vaccine provided is not made immune instead make more disease because its hygiene of vaccine. Circulation of Spurious vaccines make some state institutions such as the BPOM and BPKN must intervene in order to provide protection to the consumer (goods consumer) . In accordance with the authority that has been mandated to the BPOM and BKPN expected can do good supervision during production, labeling, marketing and supervision at the time have been circulating in community. law protection by BPOM and BPKN very important for consumers / users because people are often given the wrong information by business people. For that then law (rules) must provide space for consumers to take legal actions in restoring her/his own rights have been impaired due to consumption of these spurious vaccines.